ELECTORAL INTEGRITY AT STAKE? ISLAMIC LAW AND INDONESIAN LEGISLATION ON VOTE TRADING - Harahap, Najwa Khalilah; Marpaung, Arifin; Hafsah, Aulia; Indah, Usna Nur; Nabilah, Siti Luthfiyah (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyse the comparison of buying and selling voting rights in general elections from the perspective of Islamic law and Indonesian national law. The buying and selling of voting rights is an act that involves the exchange of voting rights for a certain reward, which is often considered a form of ethical and legal violation. In the context of Islamic law, this practice is viewed through the principles of sharia that emphasise justice, benefit, and the prohibition against buying and selling that contains elements of usury and gharar. Meanwhile, in the perspective of Indonesian national law, the buying and selling of voting rights is regulated by the law governing general elections, which confirms that the practice is illegal and subject to criminal sanctions. This study uses a qualitative method with a descriptive-analytical approach to outline the views of the two legal systems on the buying and selling of voting rights. The results show that in both Islamic law and Indonesian national law, the buying and selling of voting rights is viewed as illegitimate and violates the principles of justice. This research provides recommendations for increasing public understanding and awareness of the importance of maintaining the integrity of voting rights in general elections as well as stricter law enforcement to prevent the practice of buying and selling voting rights.